2014
DOI: 10.4172/2155-9880.1000309
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Thrombus Aspiration Catheter Trapped in Coronary Artery Due To Rupture of its Main Shaft and Twisting Over the Wire

Abstract: We report a novel complication that arose while treating a 54 year old man with acute inferior ST elevation segment myocardial infarction. It was decided to perform thrombus aspiration prior to balloon angioplasty. However, after aggressive maneuvers to cross the tight lesion in order to suck the distal thrombus, a novel complication was encountered. The Thrombus Aspiration Catheter (TAC) got stuck in the coronary artery. When the whole apparatus was pulled out, it was realized that the guidewire cut the main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…While there are various case reports on surgical retrieval of the retained hardware, 5-7 there are only a few case reports on mechanical complications with thrombus aspiration devices. Akgullu et al 8 reported a case of a thrombus aspiration catheter trapped in a coronary artery due to rupture of its main shaft and twisting over the wire while attempting to cross a tight lesion to aspirate a distal thrombus, and the whole system was percutaneously removed with pull. Taguchi et al 9 reported an inadvertent coronary endarterectomy during aspiration thrombectomy with a thrombus aspiration catheter in a patient with acute coronary syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…While there are various case reports on surgical retrieval of the retained hardware, 5-7 there are only a few case reports on mechanical complications with thrombus aspiration devices. Akgullu et al 8 reported a case of a thrombus aspiration catheter trapped in a coronary artery due to rupture of its main shaft and twisting over the wire while attempting to cross a tight lesion to aspirate a distal thrombus, and the whole system was percutaneously removed with pull. Taguchi et al 9 reported an inadvertent coronary endarterectomy during aspiration thrombectomy with a thrombus aspiration catheter in a patient with acute coronary syndrome.…”
Section: Discussionmentioning
confidence: 99%